Effect of dietary approaches to stop hypertension and curcumin co-administration on glycemic parameters in polycystic ovary syndrome: An RCT - Tayebeh Zohrabi; Azadeh Nadjarzadeh; Sara Jambarsang; Mohammad Hasan Sheikhha; Abbas Aflatoonian; Hassan Mozaffari-Khosravi (International Journal of Reproductive BioMedicine)
Abstract Background: Polycystic ovary syndrome (PCOS) is an endocrine disorder that can lead to major reproductive and metabolic complications. Management of glycemic parameters is an important step to improve the symptoms of PCOS. Objective: This study aims to evaluate the effects of the dietary approaches to stop hypertension (DASH) diet and curcumin (Cur) co-administration on glycemic parameters in normal weight and overweight/obese women with PCOS undergoing in vitro fertilization. Materials and Methods: In this double-blind randomized clinical study, 104 infertile women with PCOS were divided into 4 intervention groups considering treatment conditions and body mass index. They received 500 mg twice daily of Cur or placebo (Pls) along with DASH or a standard diet (St) based on macronutrient composition (52% carbohydrate, 18% protein, and 30% fat) for 12 wk, (DASH + Cur, DASH + Pls, St + Cur, St + Pls). The effect of these interventions on fasting blood sugar and insulin levels, insulin resistance (IR), and insulin sensitivity were determined. Results: Participants adhered to the intervention protocol ( > 80%). Insulin levels in the supplement intervention (Cur + diet) decreased significantly in the crude model. They remained significant even after adjusting for confounding variables in adjusted models (body mass index classification, energy difference, age, and physical activity levels at the baseline) ( β = -45.3, 95% CI [-73.23, -17.46], p = 0.002). Homeostasis model assessment of IR decreased significantly in the supplement intervention even after controlling for confounding factors in adjusted models. Changes in fasting blood sugar and insulin sensitivity were not significant in either the crude or adjusted models. Conclusion: The study results show that adding Cur to the diet can positively reduce insulin levels, improve IR, and lead to faster recovery of hyperinsulinemia. Cur supplementation with a healthy diet has synergistic beneficial effects on glycemic parameters. Larger clinical trials with longer durations are needed to confirm these results.